Formação continuada de professores (as) de Educação Física em Contagem/MG: narrar a experiência, escrever a aula - Aline Borges Moreira Dias (2020)
This training memorial brings reports of life, academic and professional experiences of a physical education teacher from the municipal education system of Contagem with an emphasis on the years 2018, 2019 and 2020: period when she was a master's student in the Professional Master's Program in Physical Education Scholar, physical education teacher at Albertina Alves do Nascimento Municipal School, trainer and member of the “Collective of Physical Education Teachers who narrate their Knowledge and Practice”. Part of the story narrated in this memorial is the result of the constitution of a collective of physical education teachers from the municipal network of Contagem, part of a continuing education action that aimed to create pedagogical narratives – “pedagogical popcorn” (CAMPOS and PRADO 2013) - short texts that they report cases / events in the teaching routine and bring up reflections on teaching practices, experiences, knowledge and actions produced in schools and physical education classes. The narrative is an invitation to teachers and managers of Brazilian public education to think about the continuing education formats that have been implemented in Brazil and their relationship with teaching practice and how these spaces have been constituted as a privileged moment for collective dialogue and exchange of experiences on pedagogical practice among peers.